Development of Learning Media Based on Virtual RealityIn the Subject Object-Oriented Programming Improving Learning Outcomes of RPL Students at SMK Negeri 2 Bangkalan - Moh Rochman Wahid Maulana; Supari Muslim; I Gusti Putu Asto Buditjahjanto; Bagus Dwi Cahyono (LPPM NAROTAMA UNIVERSITY, Indonesia, 2019)
AbstractThe research objectives are: (1) analyzing the validity of virtual reality-based learning media on the subjects of object-oriented programming; (2) analyze the implementation of object-oriented programming learning using virtual reality-based learning media; (3) analyze the learning activities of Bangkalan Vocational High School 2 students on object oriented programming subjects using virtual reality based learning media; (4) analyze learning outcomes in the cognitive, affective, and psychomotor domains on object oriented programming subjects; and (5) analyze the response of students of SMK Negeri 2 Bangkalan to virtual reality-based learning media. Media development is done by using Research and Development (R & D) which is validated by experts. The results of the study concluded that: (1) virtual reality-based learning media were declared valid with very good categories; (2) the implementation of virtual reality based learning media is categorized as good; (3) student learning activities in utilizing virtual reality based learning media are declared active.